A Political Economy of Trans-Border Migration Crises and Human Trafficking in Africa - Zoaka, Yusufu (Przegląd Politologiczny, 2018)
Encouraged by porous border boundaries in Africa, trafficking in persons and objects is a demand-driven global venture that has market potential for: commercial sex, cheap labour, terrorism, and drug-related crimes. Most African States, especially Nigeria, have been reputed as hardliners in encouraging these illicit trends. Chief among the motivating factors include: domestic insecurity, political instability, economic recession, and institutional failure, etc. Amongst other instigating factors however, this paper takes a cursory look at the relationship between the twin crime of trans-border migration crises and human trafficking in Nigeria, and the attendant political economic implications on the Nigerian polity. Data relied on are largely gotten from secondary sources. The paper employs the neoclassical political economic theory of migration. Findings from conceptual and theoretical reviews of literatures show that the incentive for human trafficking and migration-related offences is not only profit driven but also a fall-out from institutional failure. The paper recommends a taut border security, which can disallow border related crimes like drug and human trafficking. The paper also sues for people-oriented leadership that will eschew illicit crimes such as the above.